Comparison of the medical costs between active surveillance and other treatments for early prostate cancer in Japan using data from the PRIAS‐JAPAN study. (19th July 2022) - Kato, Takuma; Yokomizo, Akira; Matsumoto, Ryuji; Tohi, Yoichiro; Miyakawa, Jimpei; Mitsuzuka, Koji; Sasaki, Hiroshi; Inokuchi, Junichi; Matsumura, Masafumi; Sakamoto, Shinichi; Kinoshita, Hidefumi; Fukuhara, Hiroshi; et al.
Abstract : Objectives: To compare the medical costs of active surveillance with those of robot‐assisted laparoscopic prostatectomy, brachytherapy, intensity‐modulated radiation therapy, and hormone therapy for low‐risk prostate cancer. Methods: The costs of protocol biopsies performed in the first year of surveillance (between January 2010 and June 2020) and those of brachytherapy and radiation therapy performed between May 2019 and June 2020 at the Kagawa University Hospital were analyzed. Hormone therapy costs were assumed to be the costs of luteinizing hormone‐releasing hormone analogs for over 5 years. Active surveillance‐eligible patients were defined based on the following: age <74 years, ≤T2, Gleason score ≤6, prostate‐specific antigen level ≤10 ng/ml, and 1–2 positive cores. We estimated the total number of active surveillance‐eligible patients in Japan based on the Japan Study Group of Prostate Cancer (J‐CAP) study and the 2017 cancer statistical data. We then calculated the 5‐year treatment costs of active surveillance‐eligible patients using the J‐CAP and PRIAS‐JAPAN study data. Results: In 2017, number of active surveillance‐eligible patients in Japan was estimated to be 2808. The 5‐year total costs of surveillance, prostatectomy, brachytherapy, radiation therapy, and hormone therapy were 1.65, 14.0, 4.61, 4.04, and 5.87 million United States dollar (USD), respectively. If 50% and 100% of the patients in each treatment group had opted for active surveillance as the initial treatment, the total treatment cost would have been reduced by USD 6.89 million (JPY 889 million) and USD 13.8 million (JPY 1.78 billion), respectively. Conclusion: Expanding active surveillance to eligible patients with prostate cancer helps save medical costs.